Avaliação in vitro da atividade antimicrobiana de pastas endodônticas à base de extrato glicólico de Musa paradisiaca frente a Enterococcus faecalis - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The products of Musa paradisiaca (banana plantain) are used as a sedative for dental pain, healing of tooth extraction surgical wounds, gastric ulcer, hypoglycemic, antidote for snake bites, diarrhea among other indications in communities that have a tradition of using plants as alternative medicine. In Endodontics, it aspires to be an ideal intracanal medicament against resistant strains in refractory endodontic infections. Therefore, the objective of this study was to test the antimicrobial activity of Musa paradisiaca glycolic extract. To perform the experiment, the Musa paradisiaca glycolic extract replaced Polyethylene glycol 400, which is a vehicle that makes up some pastes used as Endodontic intracanal medication. Well agar diffusion test was used to evaluate the antimicrobial activity against strains of Enterococcus faecalis usually related to refractory endodontic infections. Different materials were inserted in wells in two experimental steps as characterized in the following groups. Experiment A : Group 1, Polyethylene glycol 400 (PEG 400 - negative control); Group 2, PEG 400 and calcium hydroxide (Ca(OH)2); Group 3, Musa paradisiaca Glycolic Extract (EGB); Group 4, EGB and Ca(OH)2; Group 5, 2% chlorhexidine gel (CHX - positive control). Experiment B : Group 1, PEG 400 (negative control); Group 2, PEG 400 and zinc oxide (ZnO); Group 3, PEG 400, Ca(OH)2 and ZnO; Group 4, ZnO and EGB; Group 5, EGB, Ca(OH)2 and ZnO; Group 6, CHX (positive control). After incubation, measurements of inhibition zones were performed after 18 hours with a millimeter ruler. Just EGB and ZnO paste obtained statistically significant antimicrobial activity with similar results to the positive control and was subjected to macrodilution, a finding for minimum inhibitory concentration, but no dilution of the paste was able to prevent the growth of E. faecalis. These data were treated statistically at 95% significance using the Mann-Whitney test and Descriptive Statistics. The composition of EGB was assessed by Mass Spectrometry with Electrospray Ionization and it was found that one of the major components could be maltose. Thin Layer Chromatography (CCD) was carried out in phases of ethyl acetate, dichloromethane and aqueous partition resulting from liquid/liquid held in EGB, after drying under a hood. CCD suggested the presence of flavonoids, terpenes, tannins and steroids in EGB. The Nuclear Magnetic Resonance Spectroscopy was performed in order to also propose the composition of EGB and observed a large number of signal peaks in the region concerning the glycosides, as well as peaks corresponding to the structure of terpenes and a few characteristic of steroids. The EGB showed antimicrobial activity when combined with ZnO and can be an alternative to the composition of an intracanal medication. Every new biomaterial based on ethnobotany should be carefully tested to allow its clinical applicability, which justified the relevance of this preliminary study; however physico-chemical and biocompatibility tests are essential to future employment of herbal medicines in Endodontics
Keywords: Medicação intracanal; Atividade antimicrobiana; Musa paradisiaca; Enterococcus faecalis; Intracanal medication; Antimicrobial activity; Musa paradisiaca; Enterococcus faecalis; CIÊNCIAS DA SAÚDE